HUBUNGAN POWER OTOT TUNGKAI DAN WAKTU REAKSI DENGAN KEMAMPUAN TENDANGAN DEPAN PADA PESILAT REMAJA PUTRI PSHT DI PEKANBARU - Ramadani Ramadani; Ramadi Ramadi; Aref vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the results of outhor’s observations on young female silat fighters of PSHT in Pekanbaru has found some phenomena such as: the ability of front kick that athletes did is still less than the maximum. This is caused by athletes' physical element which is not maximal such as limb muscle strength and reaction time of the athletes, so that the front kick done without power and easy to grasp. The athletes are less quick while doing front kick and pulling the kick back to its original position. The purpose of this study was to determine the relationship between leg muscle strength and reaction time with the ability of front kicks on young female PSHT silat fighters in pekanbaru. This research was conducted by using correlation research design that aims to find out how far the variables on a factor associated with other factors. The correlation is a statistical tool, which can be used to compare the results of measurements of two different variables in order to determine the degree of relationship between the variables. The population in this study were young female silat team of PSHT in Pekanbaru as many as 8 people. The data in this study were obtained by using aStanding Board Jump Test for limb muscle power, Reaction Time Meter for reaction time, and front kick ability test. Data were analyzed with simple product moment correlation. Based on the analysis of the correlation coefficient of rarithmetic (0.897)> rtable (0.754), thereby Ha accepted. This means there is a relationship between limb muscle power and reaction time with the ability to front kick, where the provision of the correlation of a variable with other variables is determined from rarithmetic> rtable and significant.Keywords: limb muscle power, reaction time (reaction time), front kick silat